Disability Studies, Disability Services: Would Addressing the Gap in Professional Communication Impact Implementation of the ADA? - Oslund, Christy (Disability Studies Quarterly, 2015)
The Civil Rights Movement spurred social changes that impacted many, including people with disabilities; while the ADA ideally provides the groundwork for greater accessibility, accessibility is an ideal that is not yet fully realized. The professionals in Disability Studies and those in Disability Services are working in often parallel contexts with little overlap and still very limited intentional interaction. This article suggests possible goals that deliberate coalition forming between the fields could set that would facilitate greater accessibility to educational environments, coalitions being informed in part by the specialized knowledge that each field contributes. As happened during the Civil Rights Movement, ideas and processes which begin on campus then have an opportunity to be carried out into broader social contexts, increasing equitable access beyond campus settings and more fully realizing the goals of the ADA.